Hubungan Kualitas Pelayanan Kesehatan dengan Kepuasan Pasien Rawat Jalan di Puskesmas Tawaeli: Penelitian - Dita; I Made Rio Dwijayanto; Masri Dg. Taha (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Health service quality is a key determinant of patient satisfaction at primary health care facilities.. Suboptimal services, such as long waiting times, ineffective communication, and limited facilities, can reduce patients’ perceptions of service quality. Community Health Centers (Puskesmas) as primary health care providers are required to deliver fast, accurate, and high-quality services. This study was conducted to examine the association between service quality and outpatient satisfaction at the Tawaeli Community Health Center. Methods: A cross-sectional quantitative approach was used in this study, with the population consisting of all outpatients at Tawaeli Community Health Center, with a sample of 56 respondents selected using accidental sampling. Data were collected using service quality and patient satisfaction questionnaires. Data were analyzed through univariate and bivariate statistical procedures, with the Chi-Square test applied to assess the relationship between variables. Results:Most respondents rated the service quality as fairly good (78.6%), while the majority of patients reported being dissatisfied (83.9%). The Chi-Square test showed a p-value of 0.000 (p<0.05). Conclusion: There is a significant relationship between service quality and outpatient satisfaction at Tawaeli Community Health Center. Recommendation: Improvements in service timeliness, communication, and facility adequacy are recommended to enhance patient satisfaction.